2015
DOI: 10.1186/s13072-015-0018-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ccr4-Not complex in heterochromatin formation at meiotic genes and subtelomeres in fission yeast

Abstract: BackgroundHeterochromatin is essential for chromosome segregation, gene silencing and genome integrity. The fission yeast Schizosaccharomyces pombe contains heterochromatin at centromeres, subtelomeres, and mating type genes, as well as at small islands of meiotic genes dispersed across the genome. This heterochromatin is generated by partially redundant mechanisms, including the production of small interfering RNAs (siRNAs) that are incorporated into the RITS protein complex (RNAi-Induced Transcriptional Sile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
59
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 68 publications
11
59
1
Order By: Relevance
“…6A as DSRx3-2). Tandem DSRs promote the selective degradation of meiotic mRNAs expressed during vegetative growth of fission yeast, via their recognition by the YTHdomain protein Mmi1 (Harigaya et al 2006;Yamashita et al 2012), which interacts with the nuclear exosome and with the Ccr4-Not complex (Cotobal et al 2015;Ukleja et al 2016). During meiosis, Mmi1 is sequestered by a DSR-containing lncRNA transcribed at the sme2 locus (Harigaya et al 2006;Shichino et al 2014), allowing stabilization of DSR-containing meiotic mRNAs.…”
Section: Prt Lncrna Contains Multiple Potential Dsr Sequencesmentioning
confidence: 99%
“…6A as DSRx3-2). Tandem DSRs promote the selective degradation of meiotic mRNAs expressed during vegetative growth of fission yeast, via their recognition by the YTHdomain protein Mmi1 (Harigaya et al 2006;Yamashita et al 2012), which interacts with the nuclear exosome and with the Ccr4-Not complex (Cotobal et al 2015;Ukleja et al 2016). During meiosis, Mmi1 is sequestered by a DSR-containing lncRNA transcribed at the sme2 locus (Harigaya et al 2006;Shichino et al 2014), allowing stabilization of DSR-containing meiotic mRNAs.…”
Section: Prt Lncrna Contains Multiple Potential Dsr Sequencesmentioning
confidence: 99%
“…At the same time, heterochromatic transcripts are degraded by RNAi. A link between various RNA degradation machineries and H3K9me at meiotic genes was also recently reported (Hiriart et al 2012;Zofall et al 2012;Egan et al 2014;Chalamcharla et al 2015;Cotobal et al 2015;Tucker et al 2016). Several of those studies suggested a direct recruitment of the H3K9 methyltransferase by different RNA degradation machineries to deposit H3K9me.…”
mentioning
confidence: 99%
“…XND-1 protein sequence provides no hints as its function, although its localization to autosomes in the developing and adult germ cells hints at a role as a chromatin regulator. The association of Nanos proteins with the CCR4/ NOT complex that recently was shown to regulate heterochromatic loci in Saccromyces pombe 35 raises the tantalizing possibility that Nanos family members may accordingly facilitate heterochromatinization of the germ line.…”
Section: Functional Redundancy In Germ Line Differentiation Pathwaysmentioning
confidence: 99%